Mission Accomplished San Francisco Ballet's commissions - Segal, Lewis (Dance Books Ltd., Alton,Hampshire (UK), 2008)
San Francisco Ballet's commissions "New Works Festival" consisting often world premieres on three programmes, created by a constellation of well-known international ballet choreographers, as well as artist attached to this and other companies, plus major moderns accustomed to periodically working for classical ensembles.